Applying Computer Integrated Manufacturing for Productivity Improvement: A Literature Review - Dudin, Sa; Ginting, Rosnani; Ishak, Aulia (Jurnal Sistem Teknik Industri, 2021)
In this era of globalization, information technology, especially through the use of computer technology (program and software) is developing rapidly and has aN enormous impact on the manufacturing industry to support companies as a solving problems tool related to manufactured products that rely on input, process, and output, as well as Increasing effectiveness, efficiency, and productivity. The purpose of this study is to review various literature regarding the application of Computer Integrated Manufacturing (CIM) in the manufacturing company. Also, the scope of this study is to discuss and analyse in depth the related articles through the identification of scientific publications from 2001 to 2021, published in databases and electronic journals in English, and 30 items selected.